Microbial diversity, autotrophic- and heterotrophic processes in Mn-rich marine sediments - Sebastian Silva-Solar; Marit R. van Erk; Gilad Antler; Katrin Knittel; Subhayit Basu; Dirk de Beer (Frontiers in Marine Science, 2025)
Marine microbial ecology aims to link microbial communities to the geochemical processes they drive. Molecular techniques have provided a view of the huge complexity of microbial communities and their metabolic potential, however, the information these approaches give about the geochemical processes is limited. Here, we combined geochemical and 16S rRNA amplicon sequencing analyses to spatially link dominant microbial taxa with geochemical processes in deep-sea sediments of the Gulf of Aqaba. The fine-grained aeolian sediments are diffusion controlled, allowing precise localization of the stratified geochemical processes in well-defined zones by transport-reaction modeling. Geochemical depth profiles and fluxes showed aerobic heterotrophy, nitrification, aerobic Mn-oxidation, denitrification, and anaerobic Fe oxidation to occur in sequence from upper to deeper sediment layers. Although chemoautotrophic processes were significant, 90% of the redox processing was driven by heterotrophy on organic carbon input. The microbial community composition also showed a clear stratification. The oxic zone was dominated by typical aerobes, while anaerobes were largely absent, as expected. Remarkably, the anoxic zone was inhabited by many aerobic bacteria, in addition to the anaerobic community. A narrow brown band enriched in solid-phase Mn-oxide was observed at 2-3 cm depth, where downward diffusing O 2 and upward diffusing Mn 2+ overlapped. Here, members of the family Ca . Scalinduaceae peaked, suggesting involvement in Mn oxidation or -reduction. Dominant families above the band were Woeseiaceae , Nitrospiraceae , and Nitrosococcaceae , whereas below the band Desulfosarcinaceae , Desulfatiglandaceae , Methylomirabilaceae , and Anaerolineaceae dominated. While Ca. Scalinduaceae peaked in the Mn-oxide band, none of the other dominant families were exclusively linked to zones with specific geochemical processes. Our approach did not resolve relations between the geochemical processes and the dominant members of the community unambiguously, but characterized a unique habitat and leads to the formulation of new hypotheses, including the occurrence of cryptic cycling.

A systematic review of the land use change effects on ant diversity in Neotropics - Icaro Wilker; Antônio C.M. Queiroz; Carla R. Ribas; Maria Santina C. Morini; Chaim J. Lasmar; Fernando A. Schmidt; Rodrigo M. Feitosa; Anselmo Nogueira; Fabrício B. Baccaro; Mônica A. Ulysséa; Thiago Izzo; Lucas N. Paolucci; et al. (Biological Conservation, 2024)

Operando FTIR-ATR with molecular dynamic simulations to understand the diffusion mechanism of waste tire-derived pyrolytic oil for asphalt self-healing - Gonzalo R. Quezada; Camilo Solar; Jorge H. Saavedra; Karla Petit; Francisco J. Martin-Martínez; Luis E. Arteaga-Pérez; José Norambuena-Contreras (Fuel, 2024)

Isolation drives species gains and losses of insect metacommunities over time in a mountaintop forest archipelago - Pedro Giovâni da Silva; Marina do Vale Beirão; Flávio Siqueira de Castro; Lucas Neves Perillo; Flávio Camarota; Ricardo R. C. Solar; Geraldo Wilson Fernandes; Frederico de Siqueira Neves (Journal of Biogeography, 2023)
Aim We evaluated the effects of forest island size, isolation and area in the landscape driving temporal changes of insect biodiversity in a mountaintop forest archipelago. We expected that (i) in smaller, less isolated forest islands, changes in insect composition are more prominent, primarily driven by gains over time; (ii) more forest in the landscape leads to increased gains of vagile species over time, regardless of forest island size and isolation; (iii) less vagile groups undergo heterogenisation, while highly vagile groups experience homogenisation due to differing dispersal capabilities. Location Espinhaço Range Biosphere Reserve, Brazil. Taxon Insects. Methods We used ants, dung beetles, bees, wasps and butterflies as study models to represent a gradient of low‐to‐high dispersal capability. We evaluated the colonisation‐ and extirpation‐resultant components of temporal β‐diversity using area‐ and isolation‐related variables as predictors. Results Distinct colonisation‐ and extirpation‐resultant homogenisation and heterogenisation processes are acting according to each insect group, likely due to different dispersal capabilities. Species losses dominated in ants, with widespread and rare species being lost. Butterflies gained species, represented mainly by widespread species, leading to an increased colonisation‐resultant homogenisation. Distance to neighbouring forest islands was the underlying predictor affecting the temporal β‐diversity of insect groups, and also species gains and losses but differently according to the survey period. Effects of the forest amount in the landscape increased the temporal β‐diversity of bees and butterflies but decreased that of ants, dung beetles and wasps. Main Conclusions These findings provide valuable biogeographic insights into the complex interactions between forest island characteristics, landscape attributes, and dispersal capabilities that shape the temporal dynamics of insect biodiversity on mountaintops. Conserving the forest amount in the landscape and keeping forest connectivity among forest islands are necessary because the temporal dynamics of local colonisation and extirpation can depend on the organisms' dispersal capability.

Ants of Brazil: an overview based on 50 years of diversity studies - Rodrigo M. Feitosa; Gabriela P. Camacho; Thiago S. R. Silva; Mônica A. Ulysséa; Natalia Ladino; Aline M. Oliveira; Emília Z. Albuquerque; Fernando A. Schmidt; Carla R. Ribas; Anselmo Nogueira; Fabrício B. Baccaro; Antônio C. M. Queiroz; et al. (Systematics and Biodiversity, 2022)

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Patterns of diversity in a metacommunity of bees and wasps of relictual mountainous forest fragments - Lucas Neves Perillo; Newton Pimentel de Ulhôa Barbosa; Ricardo R. C. Solar; Frederico de Siqueira Neves (Journal of Insect Conservation, 2020)

Ant removal distance, but not seed manipulation and deposition site increases the establishment of a myrmecochorous plant - Tiago V. Fernandes; Lucas N. Paolucci; Ricardo R. C. Solar; Frederico S. Neves; Ricardo I. Campos (Oecologia, 2020)

Different trophic groups of arboreal ants show differential responses to resource supplementation in a neotropical savanna - Laila F. Ribeiro; Ricardo R. C. Solar; Tathiana G. Sobrinho; Dalana C. Muscardi; José H. Schoereder; Alan N. Andersen (Oecologia, 2019)

Second rate or a second chance? Assessing biomass and biodiversity recovery in regenerating Amazonian forests - Gareth D. Lennox; Toby A. Gardner; James R. Thomson; Joice Ferreira; Erika Berenguer; Alexander C. Lees; Ralph Mac Nally; Luiz E. O. C. Aragão; Silvio F. B. Ferraz; Julio Louzada; Nárgila G. Moura; Victor H. F. Oliveira; et al. (Global Change Biology, 2018)
Secondary forests (SFs) regenerating on previously deforested land account for large, expanding areas of tropical forest cover. Given that tropical forests rank among Earth’s most important reservoirs of carbon and biodiversity, SFs play an increasingly pivotal role in the carbon cycle and as potential habitat for forest biota. Nevertheless, their capacity to regain the biotic attributes of undisturbed primary forests (UPFs) remains poorly understood. Here, we provide a comprehensive assessment of SF recovery, using extensive tropical biodiversity, biomass, and environmental datasets. These data, collected in 59 naturally regenerating SFs and 30 co‐located UPFs in the eastern Amazon, cover >1,600 large‐ and small‐stemmed plant, bird, and dung beetles species and a suite of forest structure, landscape context, and topoedaphic predictors. After up to 40 years of regeneration, the SFs we surveyed showed a high degree of biodiversity resilience, recovering, on average among taxa, 88% and 85% mean UPF species richness and composition, respectively. Across the first 20 years of succession, the period for which we have accurate SF age data, biomass recovered at 1.2% per year, equivalent to a carbon uptake rate of 2.25 Mg/ha per year, while, on average, species richness and composition recovered at 2.6% and 2.3% per year, respectively. For all taxonomic groups, biomass was strongly associated with SF species distributions. However, other variables describing habitat complexity—canopy cover and understory stem density—were equally important occurrence predictors for most taxa. Species responses to biomass revealed a successional transition at approximately 75 Mg/ha, marking the influx of high‐conservation‐value forest species. Overall, our results show that naturally regenerating SFs can accumulate substantial amounts of carbon and support many forest species. However, given that the surveyed SFs failed to return to a typical UPF state, SFs are not substitutes for UPFs.

The deadly route to collapse and the uncertain fate of Brazilian rupestrian grasslands - G. Wilson Fernandes; N. P. U. Barbosa; B. Alberton; A. Barbieri; R. Dirzo; F. Goulart; T. J. Guerra; L. P. C. Morellato; R. R. C. Solar (Biodiversity and Conservation, 2018)

Vegetation cover of Brazil in the last 21 ka: New insights into the Amazonian refugia and Pleistocenic arc hypotheses - Daniel M. Arruda; Carlos E. G. R. Schaefer; Rúbia S. Fonseca; Ricardo R. C. Solar; Elpídio I. Fernandes‐Filho (Global Ecology and Biogeography, 2018)
Aim The two main hypotheses about the Neotropical palaeovegetation, namely that of Amazonian refugia by Haffer and of the Pleistocene arc by Prado and Gibbs, are still constantly debated. We offer new insights on this debate using ecological niche modelling with combined climate–soil predictors to test both hypotheses, reconstruct the palaeovegetation of the Last Glacial Maximum (LGM; 21 ka) and Mid‐Holocene (Mid‐H; 6 ka) and indicate the configuration of refugia areas. Location Brazil. Time period Last 21 ka. Major taxa studied Biomes. Methods We modelled the environmental space of the 10 most representative biomes with the RandomForest classifier, using climate predictors from three atmospheric general circulation models (CCSM4, MPI‐ESM‐P and MIROC‐ESM) and soil predictors, the same for the different situations. Based on the consensus among the models, we reconstructed the palaeovegetation cover for LGM and Mid‐H and used fossil pollen sites to validate the reconstructions in a direct comparison. Results The climate in the past was cooler and wetter throughout most of the territory. The Amazon basin region was the most affected by climate change in the last 21 ka, with equatorial rain forest retracting to refugia areas, while the tropical rain forest (with climatic preferences similar to the Atlantic forest) expanded in the basin. In southern Brazil, the mixed forest ( Araucaria forest) shifted to lower latitudes, while the grasslands expanded. In most biomes, the greatest changes occurred in the ecotonal zones, supported by pollen fossils. Main conclusions With regard to Haffer's hypothesis, the forests of the Amazonian lowlands retreated to refugia areas, while the colder and wetter climate of the basin created a favourable niche for another type of forest, instead of savanna. The advance of dry vegetation was restricted to ecotonal conditions, preventing the formation of a continuous Pleistocene arc, predicted by Prado and Gibbs's hypothesis.

Combining climatic and soil properties better predicts covers of Brazilian biomes - Daniel M. Arruda; Elpídio I. Fernandes-Filho; Ricardo R. C. Solar; Carlos E. G. R. Schaefer (The Science of Nature, 2017)

Fire in the Amazon: impact of experimental fuel addition on responses of ants and their interactions with myrmecochorous seeds - Lucas N. Paolucci; Maria L. B. Maia; Ricardo R. C. Solar; Ricardo I. Campos; José H. Schoereder; Alan N. Andersen (Oecologia, 2016)

How pervasive is biotic homogenization in human‐modified tropical forest landscapes? - Ricardo Ribeiro de Castro Solar; Jos Barlow; Joice Ferreira; Erika Berenguer; Alexander C. Lees; James R. Thomson; Júlio Louzada; Márcia Maués; Nárgila G. Moura; Victor H. F. Oliveira; Júlio C. M. Chaul; José Henrique Schoereder; et al. (Ecology Letters, 2015)
Land‐cover change and ecosystem degradation may lead to biotic homogenization, yet our understanding of this phenomenon over large spatial scales and different biotic groups remains weak. We used a multi‐taxa dataset from 335 sites and 36 heterogeneous landscapes in the Brazilian Amazon to examine the potential for landscape‐scale processes to modulate the cumulative effects of local disturbances. Biotic homogenization was high in production areas but much less in disturbed and regenerating forests, where high levels of among‐site and among‐landscape β‐diversity appeared to attenuate species loss at larger scales. We found consistently high levels of β‐diversity among landscapes for all land cover classes, providing support for landscape‐scale divergence in species composition. Our findings support concerns that β‐diversity has been underestimated as a driver of biodiversity change and underscore the importance of maintaining a distributed network of reserves, including remaining areas of undisturbed primary forest, but also disturbed and regenerating forests, to conserve regional biota.

Erratum to: A multidisciplinary approach to enhance the conservation and use of hazelnut Corylus avellana L. genetic resources - L. Bacchetta; M. Rovira; C. Tronci; M. Aramini; P. Drogoudi; A. P. Silva; A. Solar; D. Avanzato; R. Botta; N. Valentini; P. Boccacci (Genetic Resources and Crop Evolution, 2015)

A multidisciplinary approach to enhance the conservation and use of hazelnut Corylus avellana L. genetic resources - L. Bacchetta; M. Rovira; C. Tronci; M. Aramini; P. Drogoudi; A. P. Silva; A. Solar; D. Avanzato; R. Botta; N. Valentini; P. Boccacci (Genetic Resources and Crop Evolution, 2015)

Molecular and morphological diversity of on-farm hazelnut (Corylus avellana L.) landraces from southern Europe and their role in the origin and diffusion of cultivated germplasm - P. Boccacci; M. Aramini; N. Valentini; L. Bacchetta; M. Rovira; P. Drogoudi; A. P. Silva; A. Solar; F. Calizzano; V. Erdoğan; V. Cristofori; L. F. Ciarmiello; et al. (Tree Genetics & Genomes, 2013)

Fatty acids and alpha-tocopherol composition in hazelnut (Corylus avellana L.): a chemometric approach to emphasize the quality of European germplasm - L. Bacchetta; M. Aramini; A. Zini; V. Di Giammatteo; D. Spera; P. Drogoudi; M. Rovira; A. P. Silva; A. Solar; R. Botta (Euphytica, 2013)

How does small-scale fragmentation affect litter-dwelling ants? The role of isolation - Lucas N. Paolucci; Ricardo R. C. Solar; Tathiana G. Sobrinho; Carlos F. Sperber; José H. Schoereder (Biodiversity and Conservation, 2012)

Can ants be used as indicators of environmental impacts caused by arsenic? - Carla R. Ribas; Ricardo R. C. Solar; Renata B. F. Campos; Fernando A. Schmidt; Clarisse L. Valentim; José H. Schoereder (Journal of Insect Conservation, 2012)

Hypogaeic pitfall traps: methodological advances and remarks to improve the sampling of a hidden ant fauna - F. A. Schmidt; R. R. C. Solar (Insectes Sociaux, 2010)

Organochlorine Residues in Fishes from Two Rivers in Cantabria, Spain: Implications for a Program of Otter (Lutra lutra) Reintroduction - R. Guitart; B. Martínez; E. Piqué; R. Mateo; M. Solar; M. Rodríguez (Bulletin of Environmental Contamination and Toxicology, 2005)

Radiolytic Degradation of the Herbicide Dicamba for Environmental Protection - P. Drzewicz; P. Gehringer; A. Bojanowska-Czajka; R. Zona; S. Solar; G. Nałcz-Jawecki; J. Sawicki; M. Trojanowicz (Archives of Environmental Contamination and Toxicology, 2005)